Cerebral Metabolites on the Descending Limb of Acute Alcohol: A Preliminary 1H MRS Study. (19th July 2019) - Monnig, Mollie A; Woods, Adam J; Walsh, Edward; Martone, Christina M; Blumenthal, Jonah; Monti, Peter M; Cohen, Ronald A
Abstract : Choline-containing compounds (Cho) and the summed peak of glutamate and glutamine (Glx) increased in the thalamus on the descending limb of alcohol, relative to baseline. Findings suggest neuroinflammatory and/or compensatory mechanisms in effect during the process of alcohol clearance. Abstract: Aims: Chronic alcohol use is associated with cerebral metabolite abnormalities, yet alcohol's acute effects on neurometabolism are not well understood. This preliminary study investigated cerebral metabolite changes in vivo on the descending limb of blood alcohol in healthy moderate drinkers. Methods: In a pre/post design, participants ( N = 13) completed magnetic resonance imaging (MRI) scans prior to and approximately 5 hours after consuming a moderate dose of alcohol (0.60 grams alcohol per kilogram of body weight). Magnetic resonance spectroscopy ( 1 H MRS) was used to quantify cerebral metabolites related to glutamatergic transmission (Glx) and neuroimmune activity (Cho, GSH, myo-inositol) in the thalamus and frontal white matter. Results: Breath alcohol concentration (BrAC) peaked at 0.070±0.008% (mean ± standard deviation) and averaged 0.025±0.011% directly prior to the descending limb scan. In the thalamus, Glx/Cr and Cho/Cr were significantly elevated on the descending limb scan relative to baseline. BrAC area under the curve, an index of alcohol exposure during the session, was significantly, positively associated with levels of Glx/Cr, Cho/Cr and GSH/Cr in the thalamus. GSH/Cr on the descending limb was inversely correlated with subjective alcohol sedation. Conclusions: This study offers preliminary evidence of alcohol-related increases in Glx/Cr, Cho/Cr and GSH/Cr on the descending limb of blood alcohol concentration. Findings add novel information to previous research on neurometabolic changes at peak blood alcohol in healthy individuals and during withdrawal in individuals with alcohol use disorder.